Spatial variability of water quality of wells in Wadi Hanifa applied study onWadi Hanifa in Darayya Governorate - Al Mubarak, Hasaa Abd El Aziz; Al Shihri, Reem (Journal of natural sciences, life and applied sciences, 2018)
This study was carried out for the Wadi Hanifa wells in Al-Deraiya area to assess their suitability for human and agricultural use. The researcher collected 7 samples of well water for chemical analysis and evaluation of quality as determined by the Saudi Standards and Metrology Authority. After the chemical analysis of the samples of the study, the acidity ratios in all samples were acceptable for agricultural uses and irrigation projects in accordance with Saudi standards. The results of the salinity analysis showed that most of the samples of the study showed a higher salinity rate than human and agricultural use, which necessitates good drainage of the soil and cultivation of high salt tolerant crops. The results of analysis of chloride and sulfate were acceptable for irrigation and agriculture, Where the ratio exceeds the standard of Saudi Arabia, which necessitates the need for limited chemical treatment of this water.
Keywords: contrast; Wadi Hanifa; well water; Diriyah